1999
DOI: 10.18002/pol.v0i9.575
|View full text |Cite
|
Sign up to set email alerts
|

Los procesos de difusión urbana en Cantabria

Abstract: Los espacios rurales de Cantabria, tanto los situados en las periferias de las principales ciudades como los que se encuentran más alejados de ellas pero disfrutan de buena accesibilidad, están experimentando desde mediados de la década de los ochenta intensos cambios vinculados a los procesos de difusión de los fenóme-nos urbanos sobre el territorio: crecimiento de su población, ampliación del parque de viviendas principales y secundarias para uso de población neorrural y urbana e implantación de nuevas activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…These cases are two medium-sized nuclei within the Spanish national context which polarize the activities of the secondary sector and the supply of tertiary and administrative services over a metropolitan region made up of a set of urban nuclei that oscillate between 10,000 and 25,000 inhabitants and which concentrate two thirds of the population of the autonomous community of Cantabria (Figure 2). The image shows a territory with a strong anthropic charge in what some authors have identified as a process of ruurbanization (Delgado, 1999). As result of this, a vast transition space between the two main poles is developed, where the Santander -Torrelavega axis is positioned as the center and driving force of the regional economy.…”
Section: Torrelavega and Santander Two Sides Of The Same Coinmentioning
confidence: 97%
See 1 more Smart Citation
“…These cases are two medium-sized nuclei within the Spanish national context which polarize the activities of the secondary sector and the supply of tertiary and administrative services over a metropolitan region made up of a set of urban nuclei that oscillate between 10,000 and 25,000 inhabitants and which concentrate two thirds of the population of the autonomous community of Cantabria (Figure 2). The image shows a territory with a strong anthropic charge in what some authors have identified as a process of ruurbanization (Delgado, 1999). As result of this, a vast transition space between the two main poles is developed, where the Santander -Torrelavega axis is positioned as the center and driving force of the regional economy.…”
Section: Torrelavega and Santander Two Sides Of The Same Coinmentioning
confidence: 97%
“…Torrelavega, in the south west, belongs to the Besaya region and is located in a valley about eight kilometers from the Cantabrian coast where the Saja and Besaya rivers meet, favoring productive activities. Both cities are linked by the regional main road, being 25 km distant from each other, and maintain strong functional links with a high degree of interdependence (Olazábal & Bellet, 2020;Delgado, 1999). On the one hand, Santander, capital of the autonomous community, is predominantly administrative and services, and tourism plays an important role in its economy.…”
Section: Torrelavega and Santander Two Sides Of The Same Coinmentioning
confidence: 99%
“…Santander y Torrelavega son núcleos de tamaño medio dentro del contexto nacional español, y polarizan las actividades del sector secundario y la oferta de servicios terciarios y administrativos sobre una región metropolitana constituida por núcleos urbanos que oscilan entre los 10.000 y 25.000 habitantes y que concentra dos tercios de la población de la comunidad autónoma de Cantabria. Se trata de un territorio con una fuerte carga antrópica, identificado por algunos autores como un proceso de rururbanización (Delgado, 1999). Como resultado de esta evolución histórica se ha creado un vasto espacio de transición entre los dos polos principales en el que el eje Santander-Torrelavega se posiciona como centro e impulsor de la economía regional.…”
Section: El áRea Urbana Santander-torrelavegaunclassified
“…Las complejas relaciones funcionales existentes en el área urbana requieren aún de estudios pormenorizados, si bien algunos autores han enfocado sus investigaciones en comprender los procesos de difusión del continuo edificado (Delgado, 1999), o el protagonismo de las dos ciudades dentro del marco espacial del corredor (De Cos y De Meer, 2013). La importancia territorial del corredor Santander-Torrelavega es manifiesta, y así queda recogido en figuras del planeamiento territorial de la propia comunidad autónoma.…”
Section: El áRea Urbana Santander-torrelavegaunclassified
“…A partir de entonces se ha ido rompiendo de manera progresiva e ininterrumpida la tradicional dicotomía entre lo rural y lo urbano, cuyas principales consecuencias han sido, entre otras: la mezcla de usos del suelo, el incremento de la vivienda unifamiliar aislada (Herrán Alonso, 2008), el abandono de las actividades agroganaderas (Morán Alonso et al, 2017), la proliferación de autovías y carreteras y el consecuente aumento de la accesibilidad y de la movilidad diaria; y finalmente, la difusión sobre el medio rural de funciones netamente urbanas tales como la educativa, la comercial o la del ocio. En suma, hemos asistido a un proceso de intensa transformación territorial, que diferentes autores han dado en llamar difusión urbana (Indovina, 1990;Delgado Viñas, 1999;Fernández García, 2003).…”
Section: Introductionunclassified